The 1956 Hungarian revolution : a history in documents - Békés, Csaba; Byrne, Malcolm; Rainer, M. János (National Security Archive Cold War readers., 2002)
If there had been all-news television channels in 1956, viewers around the world would have been glued to their sets between October 23 and November 4. This book tells the story of the Hungarian Revolution in 120 original documents, ranging from the minutes of the first meeting of Khrushchev with Hungarian bosses after Stalin's death in 1953 to Yeltsin's declaration made in 1992. Other documents include letters from Yuri Andropov, Soviet Ambassador in Budapest during and after the revolt. The great majority of the material appears in English for the first time, and almost all come from archives that were inaccessible until the 1990s.